MODEL PEMBELAJARAN PENJASORKES MELALUI BERMAIN LONCAT KATAK PADA KELAS IV SEKOLAH DASAR (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2013)
The purpose of this study to produce a learning model Penjasorkes in accordance with the characteristics of the students and to contribute to the achievement of objectives pemebelajaran Penjasorkes. The data was collected using a questionnaire derived from the experts and two experts penjas learning, testing small groups (10 students), and a field test (28 students). Data such as the results of research on the quality of the products, suggestions for improvement of the product and the results of the questionnaires by students. Data analysis technique used is descriptive percent to uncover aspects koknitf, affective and psychomotor students after using the product. From the test results obtained by the expert evaluation data, expert penjas 80% (good), Learning experts I 82.66% (excellent), a Learning II 81.33% (excellent), a small test group 92.66% (very good), and field-testing 93.10% (excellent). From the available data it can be concluded that the model of learning through play Penjasorkes frog jump chilli plants utilizing this former farm can achieve pembembelajaran and can be used in fourth grade elementary school students.